2009
DOI: 10.1016/j.neuropharm.2008.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin2C receptors in the medial prefrontal cortex facilitate cocaine-induced dopamine release in the rat nucleus accumbens

Abstract: A functional balance between excitatory and inhibitory control over dopamine (DA)-dependent behavioral and neurochemical effects of cocaine is afforded by the serotonin2C receptor (5-HT2CR) located within the ventral tegmental area and the nucleus accumbens (NAc). The 5-HT2CR located in the medial prefrontal cortex (mPFC) has also been shown to inhibit cocaine-induced behaviors perhaps through inhibition of DA function in the NAc. Using in vivo microdialysis in halothane-anesthetized rats, we tested this hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
43
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 44 publications
9
43
2
Order By: Relevance
“…Particularly, a role for 5-HT 3 receptors in the regulation of accumbens dopamine has suggested that this may be a pharmacological target for treating aspects of substance abuse (Di Matteo et al, 2008; McBride et al, 2004; Weiss et al, 2001). In contrast to most 5-HT receptors, 5HT 2C receptors exert tonic inhibitory control over dopamine release in the nucleus accumbens, although enhancing effects that are indirectly mediated through actions in the medial prefrontal cortex have also been reported (Bubar and Cunningham, 2008; Leggio et al, 2009). Certain drugs of abuse, such as cocaine, increase 5-HT as well as dopamine in the nucleus accumbens (Andrews and Lucki, 2001; Parsons et al, 1995).…”
Section: Crf Regulation Of the Drn-5-ht System: Potential Link Tomentioning
confidence: 99%
“…Particularly, a role for 5-HT 3 receptors in the regulation of accumbens dopamine has suggested that this may be a pharmacological target for treating aspects of substance abuse (Di Matteo et al, 2008; McBride et al, 2004; Weiss et al, 2001). In contrast to most 5-HT receptors, 5HT 2C receptors exert tonic inhibitory control over dopamine release in the nucleus accumbens, although enhancing effects that are indirectly mediated through actions in the medial prefrontal cortex have also been reported (Bubar and Cunningham, 2008; Leggio et al, 2009). Certain drugs of abuse, such as cocaine, increase 5-HT as well as dopamine in the nucleus accumbens (Andrews and Lucki, 2001; Parsons et al, 1995).…”
Section: Crf Regulation Of the Drn-5-ht System: Potential Link Tomentioning
confidence: 99%
“…Neurochemically, 5-HT 2C receptors tonically inhibit dopamine release in the frontal cortex, while 5-HT 2A receptor stimulation increases dopamine release in the frontal cortex (Gobert and Millan 1999; Gobert et al 2000; Millan et al 1998). However, a recent report shows that injections of the 5-HT 2C agonist RO 60-0175 into the medial prefrontal cortex of rats enhance dopamine outflow in nucleus accumbens caused by cocaine administration (Leggio et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Among the various 5-HT receptor subtypes, several studies point to the potential involvement of 5-HT2 receptor family (Auclair et al, 2010;Leggio et al, 2009aLeggio et al, , 2009bNavailles et al, 2008). Moreover, 5-HT2A and the 5-HT2C receptors have been shown to modulate the behavioral effects of cocaine (Bubar and Cunningham, 2006;Fletcher et al, 2004;Grottick et al, 2000;Muller and Huston, 2006;Nic Dhonnchadha et al, 2009).…”
Section: Introductionmentioning
confidence: 99%